Integrating English for Academic Writing Virtual Lab Setting in Pre-Service Math and Science Teacher Education Programs - Haggag Mohamed Haggag (European Scientific Journal, ESJ, 2022)
This research focuses on identifying the effect of integrating English for academic writing virtual lab setting in pre-service math and science teacher education programs. Four instruments were utilized in the different process of the research and the test was reported in the results. It utilized English for academic writing questionnaire to identify the academic writing skills needed for the participants, while a virtual academic writing module was used in the instruction of the target skills. English was utilized for the academic writing test and its rubric was used in the pre-post testing of the participants and their assessment. The participants were pre-service students (N=58) from math and science departments at Hurghada Faculty of Education, South Valley University, Egypt. Using a one-group quasi-experimental design, the research followed a pre and post testing procedure before and after applying the virtual academic writing lab. Results of the study were obtained quantitatively and qualitatively through the test of academic writing and the reflection sheet, respectively. Quantitative results showed that there were significant mean differences between participants' scores at level 0.05≥ in the pre and post testing procedure. These differences were in favor of the post testing of both basic academic writing concepts’ variable and academic writing skills variable (000), as well as the total score of participants’ academic writing (sig .002). Qualitative results also showed the positive attitudes of the participants and their satisfaction with the online module based on the feedback provided during the writing process. Recommendations of the research included integrating online virtual writing labs in pre-service math and science teachers’ education programs as well as integrating academic writing in their academic English courses.